Pharmaceutical provision of affected individuals in conditions of special period - Gudzenko, Andrii (Actual Problems of Medicine and Pharmacy, 2021)
Studied the pharmaceutical support of affected individuals in the conditions of special period. The meaningful meaning is determined: special period; affected individuals and their close relatives. Particularities of the pharmaceutical provision of affected contingents of the population in the conditions of special period were studied. Proved that the analysis of the experience of economically developed countries is useful for the formation of a powerful and effective healthcare system in Ukraine for the pharmaceutical provision of affected and privileged categories of citizens in emergency situations. The necessity of further researches in the field of pharmaceutical provision of persons who suffered in the conditions of the special period is substantiated.